Effects of tariffs and sanitary barriers on high- and low-value poultry trade - Peterson, Everett B.; Orden, David (International Food Policy Research Institute, 2004)
A competitive partial-equilibrium spatial model with heterogeneous goods is constructed to evaluate effects of the removal of tariffs, tariff-rate quotas, and sanitary regulations on world poultry trade. The model distinguishes between high-value" (mostly white meat) and "low-value" (mostly dark meat) poultry products and simulates the trade flows between eight exporting and importing countries and regions. Removing all barriers simultaneously has larger impact on trade than only removing tariffs and tariff-rate quotas. Imposition of sanitary barriers against US products by Russia shifts trade flows, but does not have large net impacts on US producers." -- Authors' Abstract